2003
DOI: 10.1073/pnas.1733208100
|View full text |Cite
|
Sign up to set email alerts
|

The VirD2 pilot protein of Agrobacterium -transferred DNA interacts with the TATA box-binding protein and a nuclear protein kinase in plants

Abstract: The bacterial virulence protein VirD2 plays an important role in nuclear import and chromosomal integration of Agrobacteriumtransferred DNA in fungal, plant, animal, and human cells. Here we show that in nuclei of alfalfa cells, VirD2 interacts with and is phosphorylated by CAK2Ms, a conserved plant ortholog of cyclindependent kinase-activating kinases. CAK2Ms binds to and phosphorylates the C-terminal regulatory domain of RNA polymerase II largest subunit, which can recruit the TATA box-binding protein.VirD2 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
4
2
2

Relationship

2
6

Authors

Journals

citations
Cited by 85 publications
(63 citation statements)
references
References 62 publications
(82 reference statements)
3
60
0
Order By: Relevance
“…Cells were harvested by centrifugation and then resuspended and sonicated in lysis buffer (50 mM NaH 2 PO 4 , 300 mM NaCl, 1 mM phenylmethylsulfonylfluoride, 0.1 mM benzamidine, 10 µg/mL aprotinin, and 10 µg/mL leupeptin, pH 8.0). The cell lysate was subjected to centrifugation (Sorvall HB-4 rotor; 16,500g for 30 min at 4°C), and the cleared extract was used for affinity purification on glutathione-Sepharose 4B (Amersham Biosciences) as described (Umeda et al, 1998;Bakó et al, 2003). E. coli BL21 (DE3) pLysS cells carrying pET201-Trx-CDKDs-His 6 , pET201-Trx-CyclinH;1-His 6 , and pET201-Trx-CDKF;1-His 6 (see Supplemental Methods 1 online) were disrupted by sonication in lysis buffer, and upon centrifugation the cleared extracts were affinity purified on nickel-nitriloacetic acid agarose (Qiagen) according to the manufacturer's instruction.…”
Section: Purification Of Arabidopsis Proteins Expressed In Escherichimentioning
confidence: 99%
“…Cells were harvested by centrifugation and then resuspended and sonicated in lysis buffer (50 mM NaH 2 PO 4 , 300 mM NaCl, 1 mM phenylmethylsulfonylfluoride, 0.1 mM benzamidine, 10 µg/mL aprotinin, and 10 µg/mL leupeptin, pH 8.0). The cell lysate was subjected to centrifugation (Sorvall HB-4 rotor; 16,500g for 30 min at 4°C), and the cleared extract was used for affinity purification on glutathione-Sepharose 4B (Amersham Biosciences) as described (Umeda et al, 1998;Bakó et al, 2003). E. coli BL21 (DE3) pLysS cells carrying pET201-Trx-CDKDs-His 6 , pET201-Trx-CyclinH;1-His 6 , and pET201-Trx-CDKF;1-His 6 (see Supplemental Methods 1 online) were disrupted by sonication in lysis buffer, and upon centrifugation the cleared extracts were affinity purified on nickel-nitriloacetic acid agarose (Qiagen) according to the manufacturer's instruction.…”
Section: Purification Of Arabidopsis Proteins Expressed In Escherichimentioning
confidence: 99%
“…However, in a recent study it was concluded that VIP1 is not important for AMT or VirE2 subcellular localization (Shi et al, 2014). VirD2 may also have a role in the targeting to the chromatin as Bakó et al (2003) reported that VirD2 bound to the TATA-box-binding protein in transformed Arabidopsis thaliana cells. In our study, we showed that both in vitro as well as in vivo, VirD2 binds to the yeast histone proteins (H2A, H2B, H3 and H4) (Figs 2 and 3) and that VirD2 translocated from Agrobacterium to yeast also binds to histone proteins (Fig.…”
Section: Discussionmentioning
confidence: 96%
“…Using yeast two-hybrid and plant-based BiFC systems, scientists have identified several plant proteins that interact with VirD2. Prominent among these plant proteins are members of the importin a family, which play a role in nuclear targeting of VirD2/T-strand complexes (Ballas and Citovsky, 1997;Bhattacharjee et al, 2008), and several different cyclophillin proteins whose role in transformation is not yet known Bakó et al, 2003).…”
Section: Screening An Arabidopsis Cdna Library For Proteins That Intementioning
confidence: 99%
“…The first of these (clone 130-14O) is cyclophilin ROC3 (At2g16600). Using yeast two-hybrid analyses, Deng et al (1998) and Bakó et al (2003) previously identified several Arabidopsis cyclophilins, including ROC3, as proteins that interact with VirD2. Finally, we identified the clone 130-6O whose protein product strongly interacts with nYFP-VirD2.…”
Section: Screening An Arabidopsis Cdna Library For Proteins That Intementioning
confidence: 99%
See 1 more Smart Citation